Young adulthood in uncertain times: The association between sense of personal control and employment, education, personal relationships and health. (June 2019) - Chesters, Jenny; Smith, Jonathan; Cuervo, Hernan; Laughland-Booÿ, Jacqueline; Wyn, Johanna; Skrbiš, Zlatko; Woodman, Dan
Young adults in Australia, and in many other advanced countries, are more likely to be highly educated but less likely to be in full-time employment than their parents were. Although insecure employment has long been a feature of labour markets, increased labour flexibility in recent decades has resulted in insecure employment becoming entrenched. In this article, we draw on data from young people in their early twenties to examine the interrelationships between work and life. Although we focus on the association between precarious employment and sense of personal control, we also examine the interrelationships between sense of personal control, education, relationships and health. Rather than experiencing a short period of insecure employment before transitioning into permanent jobs, young people now experience a 'new adulthood' characterised by extended periods of insecurity, undermining their sense of personal control. Our aim is to identify what it takes to make a secure, healthy and meaningful life.